2006
DOI: 10.3168/jds.s0022-0302(06)72600-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atmospheric Composition on Respiratory Behavior, Weight Loss, and Appearance of Camembert-Type Cheeses During Chamber Ripening

Abstract: Respiratory activity, weight loss, and appearance of Camembert-type cheeses were studied during chamber ripening in relation to atmospheric composition. Cheese ripening was carried out in chambers under continuously renewed, periodically renewed, or nonrenewed gaseous atmospheres or under a CO(2) concentration kept constant at either 2 or 6% throughout the chamber-ripening process. It was found that overall atmospheric composition, and especially CO(2) concentration, of the ripening chamber affected respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…As noted earlier, culture-dependent methods do not reflect this exponential growth of fungi because cells contained in the hyphal filaments cannot be counted on culture media and because these techniques are highly influenced by the presence of spores (19). Inaccurate evaluation of the exponential growth phase for P. camemberti was attributed to the fact that spore formation began at about day 5 (36) and was predominant between day 8 and day 12 of the ripening period (19,23). Spores can easily be separated from mycelia and form individual colonies on culture medium, while dense mycelia are difficult to spread.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, culture-dependent methods do not reflect this exponential growth of fungi because cells contained in the hyphal filaments cannot be counted on culture media and because these techniques are highly influenced by the presence of spores (19). Inaccurate evaluation of the exponential growth phase for P. camemberti was attributed to the fact that spore formation began at about day 5 (36) and was predominant between day 8 and day 12 of the ripening period (19,23). Spores can easily be separated from mycelia and form individual colonies on culture medium, while dense mycelia are difficult to spread.…”
Section: Discussionmentioning
confidence: 99%
“…In cheese ripening, as in every complex food processes, most of the control measures are performed on the basis of the expert's sensory perceptions (Perrot et al, 2004;Picque et al, 2006). The ripening expert is able to explain part of the complex reactions through his perception of quality changes.…”
Section: Operational Knowledge Modelling: Model M 1 (Development Of Smentioning
confidence: 99%
“…For example, Picque et al (2006) and Leclercq-Perlat et al (2006) reported that the ripening of soft mould-ripened cheeses was modified by the gas composition of the ripening chamber. Respiratory activity and proteolysis were increased by increasing the CO 2 concentration (to between 2 and 6%), but an excessively high level (6%) negatively influenced the appearance of the cheeses.…”
Section: Introductionmentioning
confidence: 97%